A Novel Compact CPW Multi-StopBand Filter with DGS Integrating Circular Ring Resonator. (2017) - Sghir, Elmahjouby; Errkik, Ahmed; Zbitou, Jamal; A.Tajmouati, A.Tajmouati; Abdellaouitat, Larbi El; Latrach, Mohamed
No abstract available